MODERNIZATION OF THE LAW ENFORCMENT SYSTEM: ТHE USE OF CONTEMPORARY ARTIFICIAL INTELLIGENCE TOOLS IN CRIME PREVENTION AND SUPPRESSION - Tasić, Marija; Ivanović, Aleksandar; Kesić, Tanja; Bjelovuk, Ivana (Srpska politička misao, 2025)
Law enforcement agencies represent one of the most significant users of artificial intelligence–based systems in the context of contemporary manifestations of crime. Police agencies, as well as those operating within the criminal justice system, already make extensive use of various systems, software, and tools in the field of crime prevention and suppression. This article analyzes the application of existing artificial intelligence systems by law enforcement agencies through a critical review of relevant academic and professional literature, along with an illustration of examples of systems, software, and tools used in the operational context. In the first chapter, the possibilities of applying artificial intelligence systems in the field of crime prevention are presented through an overview of specific software for predicting crime and the criminal behavior of individuals, including risk assessments of recidivism and repeat victimization. In the second chapter, the possibilities of applying specific systems, software, and tools in the field of crime suppression are presented, starting from the receipt of criminal reports, the preparation and planning of criminal investigations, and up to their application in the area of international police cooperation. Finally, the article points out the controversies surrounding the use of artificial intelligence by law enforcement agencies, considering several aspects such as technological, legal, ethical, and social.